Factors associated with dietary supplement use by people who exercise at gyms - Lacerda, Francisca Mirian Moura; Carvalho, Wellington Roberto Gomes; Hortegal, Elane Viana; Cabral, Nayra Anielly Lima; Veloso, Helma Jane Ferreira (Revista de Saúde Pública, 2015)
OBJECTIVE To assess the factors associated with the use of dietary supplements by people who exercise at gyms.METHODS A cross-sectional study with a sample defined by convenience, considering the number of gyms registered in the Conselho Regional de Educação Física (Regional Council of Physical Education) of Sao Luis, MA, Northeastern Brazil, from July 2011 to July 2012. The final sample comprised 723 individuals who exercise at gyms. The dependent variable was supplement use, and the explanatory variables were length of time and motivation of the physical exercises, duration, goal and self-perception of training, weekly frequency of gym attendance, sex, age, educational attainment, self-perception of body weight, smoking and self-perception of diet. The association between variables was analysed by hierarchical Poisson regression based on a theoretical model.RESULTS Supplement use was reported by 64.7% of the participants. Most of the sample was male (52.6%). The most frequent age group was 20 to 39 years (74.4%). Most participants (46.1%) had been exercising for over a year. The following variables were associated with supplement use: self-perceiving body weight as below ideal (p < 0.001), smoking (p < 0.001), exercising for 7 to 12 months (p = 0.028) or more than one year (p < 0.001), spending more than two hours at the gym (p = 0.051), and perceiving training as moderate (p = 0.024) or intense (p = 0.001).CONCLUSIONS The use of supplements lacks proper professional guidance, being motivated by individuals unsatisfied with their low body weight and who perceive their workout as intense, which raises the need for monitoring this population.